The relationship between Flexible Working Arrangements (FWAs) and lecturers' productivity at public universities in Malaysia - Praveena, R Arumugam (2025)
This study explores the relationship between Flexible Working Arrangements (FWAs) and lecturers’ productivity at public universities in Malaysia. FWAs encompass remote working, hybrid working, and flexible scheduling, are increasingly adopted as strategies to enhance employee productivity. Using a quantitative, cross-sectional research design, data were collected from 230 lecturers through a structured questionnaire. The analysis was conducted using SPSS Version 26, applying descriptive statistics and Pearson correlation. The findings revealed a significant positive relationship between all three types of FWAs and employee productivity. These results suggest that when employees are provided with greater flexibility, their productivity levels are likely to improve. The study offers valuable insights for higher education institutions aiming to enhance lecturer performance through supportive and flexible work environments. It also contributes to the limited literature on FWAs in the Malaysian academic context and provides a foundation for future research in this area